Economic planning in Venezuela - Levy, Fred D. (New York : Praeger, 1968)
This book is a case study of a newly initiated planning system, the architects of Venezuelan.
Includes bibliographical references: p. 195-204.
oo 08/08/2018
Loans
Keywords: Economic planning; Venezuela